2013
DOI: 10.3389/fpsyg.2013.00483
|View full text |Cite
|
Sign up to set email alerts
|

Breath holding duration as a measure of distress tolerance: examining its relation to measures of executive control

Abstract: Recent research considers distress (in)tolerance as an essential component in the development of various forms of psychopathology. A behavioral task frequently used to assess distress tolerance is the breath holding task. Although breath holding time (BHT) has been associated with behavioral outcomes related to inhibitory control (e.g., smoking cessation), the relationship among breath holding and direct measures of executive control has not yet been thoroughly examined. The present study aims to assess (a) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 57 publications
4
28
2
Order By: Relevance
“…Rush Back also presents a moderate but statistically significant correlation with time at TLC. In a relatively similar protocol, Sütterlin et al observed a link between executive function and breath-holding time at RFC (Sütterlin et al, 2013), which was not the case in our study. In another study, self-assessed persistence with difficult tasks was not related to breath-hold time after deep breathing (Thompson-Lake et al, 2017).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Rush Back also presents a moderate but statistically significant correlation with time at TLC. In a relatively similar protocol, Sütterlin et al observed a link between executive function and breath-holding time at RFC (Sütterlin et al, 2013), which was not the case in our study. In another study, self-assessed persistence with difficult tasks was not related to breath-hold time after deep breathing (Thompson-Lake et al, 2017).…”
Section: Discussionsupporting
confidence: 51%
“…Unpleasantness and the degree of effort were evaluated in each condition using a modified version of the 'Breath-holding task-experience questionnaire' developed by Sütterlin et al on the following scales (Sütterlin et al, 2013): a) The unpleasantness experienced, on a 10-centimeter analogic visual scale (0: extremely unpleasant, 10: extremely pleasant). b) The degree of effort required to perform the task (0: absolutely no effort, 10: an extreme amount of effort)…”
Section: Protocolmentioning
confidence: 99%
“…These are mainly negative results since it is not possible to disentangle whether the difference for respiratory rate was a true response to the breath holding test or a consequence of a different pre-test end tidal pCO 2 , which was not measured. These results can, once again, be explained as a lack of influence of nicotine abstinence on the response to a biological challenge (Cosci et al, 2013, accepted for publication) but may also support a poor validity of the breath holding test as a task to assess distress tolerance (Sütterlin et al, 2013).…”
Section: Discussionmentioning
confidence: 90%
“…We expected that manipulation of time perception, a psychological factor, would affect the struggle phase duration, since prior work has shown that the length of the struggle phase depends on psychological factors such as intrinsic motivation and willingness to withstand discomfort (Godfrey & Campbell, ; Sütterlin et al, ; Thompson‐Lake et al, ). However, we did not find a significant change in the duration of the struggle phase due to time manipulation (Figure c), perhaps because the participants in this study had little experience with breath holding and a low tolerance for discomfort.…”
Section: Discussionmentioning
confidence: 99%